Polyimides as Promising Materials for Lithium-Ion Batteries: A Review - Zhang, Mengyun; Wang, Li; Xu, Hong; Song, Youzhi; He, Xiangming (Nano-Micro Letters, 2023)
Lithium-ion batteries (LIBs) have helped revolutionize the modern world and are now advancing the alternative energy field. Several technical challenges are associated with LIBs, such as increasing their energy density, improving their safety, and prolonging their lifespan. Pressed by these issues, researchers are striving to find effective solutions and new materials for next-generation LIBs. Polymers play a more and more important role in satisfying the ever-increasing requirements for LIBs. Polyimides (PIs), a special functional polymer, possess unparalleled advantages, such as excellent mechanical strength, extremely high thermal stability, and excellent chemical inertness; they are a promising material for LIBs. Herein, we discuss the current applications of PIs in LIBs, including coatings, separators, binders, solid-state polymer electrolytes, and active storage materials, to improve high-voltage performance, safety, cyclability, flexibility, and sustainability. Existing technical challenges are described, and strategies for solving current issues are proposed. Finally, potential directions for implementing PIs in LIBs are outlined. Highlights: 1 Polyimides (PIs) as coatings, separators, binders, solid-state electrolytes, and active storage materials help toward safe, high-performance, and long-life lithium-ion batteries (LIBs). 2 Strategies to design and utilize PI materials have been discussed, and the future development trends of PIs in LIBs are outlooked.